Problems of stage speech in theatre art (Journal of Philosophy Culture and Political Science, 2016)
One of the important objectives set out in this article is to analyze and study the centuries-old spiritual heritage of the Kazakh people. Start studying from history can not only learn the scientific achievements, but also provides an excellent opportunity for further progress. There is no doubt that this aspect is also applicable to the Kazakh Theater. It is well known that the theater does not develop without drama. Modern theater has become an integral part of the cultural life of the people and takes an active part in solving the historical, political, cultural, social, and cognitive problems. Thus, there is no doubt the fact that modern performances in the genre of comedy require in-depth study. Society located on a path of continuous development and modernization, always striving for the study of actual problems of art. Social and cultural situation in the modern world, the conflict in the mental development of the individual, the negative phenomena in the spiritual development of man, the economic crisis and covering all aspects of public life spiritual crisis – all these processes are naturally beginning to find its expression in the drama.
Keywords: art; theater; speech; stage speech.